Epistemologia de Paulo Freire e Edgar Morin como suporte para construção de uma proposta CTSA - Coelho da Silva Cantanhede, Severina; Rizzatti, Ivanise Maria; Cantanhede, Leonardo Baltazar (Góndola, Enseñanza y Aprendizaje de las Ciencias, 2022)
The cognitive development of students and the way of reflecting on the school environment experienced by students and teachers represent important aspects of Paulo Freire and Edgar Morin's educational concepts. These conceptions converge with Science, Technology, Society, and Environment (STSE) orientations as they configure the understanding of the world as a space of human existence, providing opportunities for the approximation between themes belonging to the student's daily lives and the surroundings of schools since the world problematized in the classroom environment is the same in its most immediate context. Considering the epistemological presuppositions of Freire and Morin, this work discusses the socioeconomic and school structure indicators that can support the construction of a proposal with STSE orientation. The research quanti-qualitative type and data collection arose from a Chemistry Degree class at the Federal Institute of Education, Science and Technology of Maranhão – IFMA/Campus Codó, using questionnaires in Likert scale, starting from the recognition of aspects of the institution, passing through the teacher and family situation until reaching the student. Results demonstrate that the institution's management already signals the overcoming of a stagnant paradigm, typical of the Brazilian school scenario in the 20th century, and the factors related to student performance in school are related to what happens outside it, such as their socioeconomic situation. Thus, knowledge of socioeconomic indicators and school structure are factors that justify the implementation of a teaching proposal with STSE bias, both for the improvement of the teaching and learning processes and for the education of a citizen capable of taking a critical, reflective, and argumentative position facing situations experienced in the daily lives of society.